THE USE OF SEMIOTICS SIGNS IN HATE SPEECH IN SOCIAL MEDIA INSTAGRAM - Resky, Feby Aulia; Nur, Muh. Safar; Budiman, Andi Nurul Annisa (Journal of English Literature and Linguistic Studies, 2025)
This study aims to analyze the semiotics of hate speech in social media instagram using the theory of Ferdinand de Saussure (1900) and Charles Sanders Peirce (1900). Semiotics is the study of signs or an epistemology about the existence or actuality of signs in society. This study aims to analyze and describe some netizens who utter hate speech that should not be released on social media instagram in the comments column of the personal account that is the object of the research. Based on the findings above, we found 5 types of hate speech that are in accordance with the theory expressed by Ferdinand de Saussure(1900) and Peirce (1900). 2 examples of hate speech used by netizens expressed by Ferdinand de Saussure include Signifier, and Signified, and 3 hate speech used by netizens expressed by Peirce include Index, Icon, and Symbols. In this study, we used descriptive qualitative research methods where this research uses naturalistic data, which is one of its main characteristics. The results of this thesis prove that based on the result of the above analysis, most netizens comment using symbolic hate speech. Specifically, a symbol is something that can stand for concepts, ideas, and items that are used as references. Less people use markers for hate speech thus a symbol can be any action, gesture, picture, sound, pattern, or occasion that communicates and transmits meaning on social media platforms like Instagram.